Richness and Impact of Invasive Alien Species Plant in Trees of Shivapuri Nagarjun National Park, Central Nepal - Karki, Rubina; Dixit, Sweta; Chaudhari, Satyam Kumar; Dhamala, Man Kumar; Bhatta, Sijar; Khadka, Dipak (Journal of Environment Sciences, 2022)
The effect of invasive species on biodiversity is a major issue of world. This study was conducted at the Shivapuri Nagarjun National Park. This study assessed the invasive species status factor associated with it and their impact on seedling and sapling of trees. Modified Whittaker Nested sampling stratifies was adopted for vegetation sampling. A total of 15 plots were taken with 195 subplots between 1409 m to 2140 m. altitudinal ranges. A total of 32 tree species and nine invasive species were recorded from the studied sites. The pine forest was having significantly (W = 3, p = 0.03) more coverage of invasive species than mixed forest, the coverage of invasive species was also significantly (W = 50, p = 0.009) more with more invasive species than plot with single invasive types. Beside this coverage was also affected by canopy cover, trampling and altitude but not significantly different. The invasive species have impact on numbers of seedling, sapling and their diversity species coverage. We recommend removing these invasive species.